T Lymphocyte Exhaustion During Human and Experimental Visceral Leishmaniasis - Costa-Madeira, Juliana C.; Trindade, Gabrielly B.; Almeida, Paulo H. P.; Silva, João S.; Carregaro, Vanessa (Frontiers in Immunology, 2022)
A key point of immunity against protozoan Leishmania parasites is the development of an optimal T cell response, which includes a low apoptotic rate, high proliferative activity and polyfunctionality. During acute infection, antigen-specific T cells recognize and eliminate the pathogen, promoting the development of an antigen-independent memory T cell response, which includes a strong ability to mount effector responses quickly after re-exposure to the parasite. The functionality of specific T cells is lost during chronic infection, resulting in inferior effector functions, poor response to specific restimulation, and suboptimal homeostatic proliferation, a term referred to as T cell exhaustion. Multiple factors, including parasite load, infection duration and host immunity, affect T lymphocyte exhaustion. These factors contribute to antigen persistence by promoting inhibitory receptor expression and sustained production of soluble mediators, influencing suppressive cell function and the release of endogenous molecules into chronically inflamed tissue. Together, these signals encourage several changes, reprogramming cells into a quiescent state, which reflects disease progression to more severe forms, and development of acquired resistance to conventional drugs to treat the disease. These points are discussed in this review.